2009
DOI: 10.1016/j.jpeds.2008.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Positive Screening on the Modified Checklist for Autism in Toddlers (M-CHAT) in Extremely Low Gestational Age Newborns

Abstract: Objective-To test the hypothesis that children born preterm are more likely to screen positive on the M-CHAT for an autism spectrum disorder.Study design-We explored the possibility that motor, vision, hearing and cognitive impairments might contribute to this increase.Results-Relative to children who could walk, the odds for screening positive on the M-CHAT was increased 23-fold for those unable to sit or stand independently and more than 7-fold for those needing assistance to walk. Compared with children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 22 publications
10
104
4
Order By: Relevance
“…Two recent studies even found a gradual increased risk of traits of ASD with shorter gestation (18,19). Screening studies in early childhood revealed that features of ASD have a disproportionally higher prevalence in the preterm compared to the general population (20)(21)(22)(23). Studies with the Modified-Checklist for Autism in Toddlers (M-CHAT) (24,25) found screening percentages between 21 and 41% (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies even found a gradual increased risk of traits of ASD with shorter gestation (18,19). Screening studies in early childhood revealed that features of ASD have a disproportionally higher prevalence in the preterm compared to the general population (20)(21)(22)(23). Studies with the Modified-Checklist for Autism in Toddlers (M-CHAT) (24,25) found screening percentages between 21 and 41% (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Since several studies indicated that the high frequency of neurological, cognitive and sensory difficulties may give rise to false-positive screening classifications for ASD (21,22,26,31), a diagnostic evaluation to confirm true rates of ASD is indicated. To our knowledge, only one study confirmed a positive ASD screen with a further assessment in late childhood: of the 15.8% children with a positive screen on the Social Communication Questionnaire (SCQ) (32), 8% was diagnosed with ASD following a psychiatric evaluation at 11 years (33).…”
Section: Introductionmentioning
confidence: 99%
“…Given the increased risk of ASDs with decreasing gestational age, it is unsurprising that we found a higher positive screening rate. Furthermore, Limperopoulos et al 9 excluded children with suspected cerebral dysgenesis, chromosomal disorders, or obvious dysmorphic features, while Kuban et al, 8 excluded children who could not complete the second edition of the Bayley Scales of Infant Development. These exclusions inevitably omitted children with severe developmental delay and potentially some with pervasive behavioural problems who could not be engaged in the test.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study found that 21% of infants (212/988) born before 28 weeks of gestation screened positive using M-CHAT (Kuban et al, 2009) as compared to 5.7% of healthy children 16-30 months old (Kleinman et al, 2008). Much higher rates of positive testing on M-CHAT were found in premature children with motor or sensory impairment (Kuban et al, 2009). It should be noted, however, that a positive CHAT test must be confirmed with more specific diagnostic tools, such as the Autism Diagnostic Observation Schedule-Generic (ADOS-G, a patient observational tool) or the Autism Diagnostic Interview-Revised (ADI-R, a parent interview tool) which provide a more reliable diagnosis for ASD.…”
Section: The Role Of Prematuritymentioning
confidence: 99%
“…Another study performed a prospective follow-up assessment on 91 ex-preterm very low birth weight (VLBW) infants (<1500 g at birth) at the mean age of 22 months and found 26% of these children to have a positive Modified Checklist for Autism in Toddlers (M-CHAT) test (Kinney et al, 2008). A more recent study found that 21% of infants (212/988) born before 28 weeks of gestation screened positive using M-CHAT (Kuban et al, 2009) as compared to 5.7% of healthy children 16-30 months old (Kleinman et al, 2008). Much higher rates of positive testing on M-CHAT were found in premature children with motor or sensory impairment (Kuban et al, 2009).…”
Section: The Role Of Prematuritymentioning
confidence: 99%